2019
DOI: 10.1088/1361-6463/ab5900
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced plume investigated by finite element modelling and scaling of particle entrainment in laser powder bed fusion

Abstract: FABBRO-Laser-induced plume investigated by finite element modelling and scaling of particle entrainment in laser powder bed fusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…This phenomenon was also pointed out experimentally by (Bidare, 2018) and suspected by (Mayi et al, 2019) using numerical simulation. During the keyhole formation and the vaporisation of the metal, a radial flow (of protective gas) directed toward the melt pool is induced Fig.…”
Section: Argon Versus Heliumsupporting
confidence: 66%
See 2 more Smart Citations
“…This phenomenon was also pointed out experimentally by (Bidare, 2018) and suspected by (Mayi et al, 2019) using numerical simulation. During the keyhole formation and the vaporisation of the metal, a radial flow (of protective gas) directed toward the melt pool is induced Fig.…”
Section: Argon Versus Heliumsupporting
confidence: 66%
“…Under argon, a large volume of vapour expands as a cloud whereas under helium it takes the form of a strongly oriented vapour beam. This suggests a faster expansion speed under helium due to its lower density (Mayi et al, 2019). In that case, the vapour is expanding freely and is less confined by the surrounding gas than in argon.…”
Section: Analysis Of the Vapour Plumementioning
confidence: 99%
See 1 more Smart Citation
“…The spattering power is measured from x-ray imaging series for bare plate experiments (Supplementary Text). The spattering is more frequent in laser powder bed fusion process because of the particle entrainment effect (23), which might lead to higher spattering power loss.…”
Section: The Scaling Parameter Ke M L Dmentioning
confidence: 99%
“…by temperature gradient mechanism [15,34,39]. Based on this metallurgical behavior, pre-solidified material underneath the melted layer is heated up rapidly upon laser irradiation, which readily expands, but is constricted by the cold and rigid portions of the solidified piece, repeated in multiple cycles [40,41]. It was also observed that when the samples were rotated around the Z axis by 45° (e.g., Figure 9b), the recoater does not suddenly meet a long section, reducing the risks of crashes.…”
Section: Manufacturing Evaluationmentioning
confidence: 99%